Molecular and morphometric analyses reveal cryptic diversity within freshwater mussels (Bivalvia: Unionidae) of the western Gulf coastal drainages of the USA. (4th May 2018) - Pieri, Anna M; Inoue, Kentaro; Johnson, Nathan A; Smith, Chase H; Harris, John L; Robertson, Clint; Randklev, Charles R
Abstract: Past geological processes and climate change affected current species distributions and the genetic structure of riverine fauna. Western Gulf of Mexico coastal rivers harbour four mussel species within the genus Fusconaia (Bivalvia: Unionida). The distributions of these species are unclear owing to their indistinguishable shell morphologies. Using molecular phylogenetic and Fourier morphometric analyses, we examined phylogenetic relationships and morphological variation among the species and made inferences about the role of past geological and climatic factors in shaping the current genetic structure and distributions of these species in the region. Our results showed the presence of three Fusconaia species within the region: Fusconaia askewi, Fusconaia chunii and Fusconaia flava . We confirmed that Fusconaia lananensis is a junior synonym of F. askewi and that F. chunii is genetically distinct from F. askewi . The Trinity River has syntopic F. flava whose morphologies are indistinguishable from those of F. chunii . Divergence-time estimates matched major geological and climatic events in the region, where climate-driven river formations during the mid-Miocene to Pleistocene caused major diversification of Fusconaia species. Knowledge gained from the present study provides a better understanding of vicariant events that shaped current species distributions and helps to identify conservation priorities that apply to the Fusconaia species.